2014
DOI: 10.17660/actahortic.2014.1044.33
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Rotation Systems for Soilborne Disease, Weed and Fertility Management in Strawberry/Vegetable Production

Abstract: Organic strawberry/vegetable producers in coastal California face soilborne disease, nutrient, and weed management challenges. In conventional systems, stringent regulations and air quality concerns make the sustainability of fumigantdependent systems uncertain. To evaluate efficacy of anaerobic soil disinfestation (ASD), mustard cake (MC) application and broccoli residue incorporation, we initiated trials at an organic farm (Org) and a conventional farm (Conv) with crop rotation (broccoli (Brassica oleracea L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…This was likely due to a combination of enhanced fertility in the early season and disease suppression in the later season. Indeed disease severity was significantly reduced with the ASD treatments (Zavatta et al, 2014). What is particularly interesting, however, is that the numbers of V. dahliae microsclerotia present in the soil were still lower in the ASD treatments almost 2 years later ( Figure 1B).…”
Section: Rotation Studymentioning
confidence: 89%
See 2 more Smart Citations
“…This was likely due to a combination of enhanced fertility in the early season and disease suppression in the later season. Indeed disease severity was significantly reduced with the ASD treatments (Zavatta et al, 2014). What is particularly interesting, however, is that the numbers of V. dahliae microsclerotia present in the soil were still lower in the ASD treatments almost 2 years later ( Figure 1B).…”
Section: Rotation Studymentioning
confidence: 89%
“…There was no significant effect of previous crop on the growth and yield response of strawberries irrespective of the disease management strategy used (see Zavatta et al, 2014, for details). However, when averaged across all previous crop treatments (fallow, broccoli and cauliflower) yields were highest in the ASD treatment with RB+MSM as the carbon source and ASD with RB only ( Figure 1A).…”
Section: Rotation Studymentioning
confidence: 99%
See 1 more Smart Citation
“…One disadvantage of anaerobic soil disinfestation is its variable weed control, (Zavatta et al 2014). In multiple California field trials anaerobic soil disinfestation has shown significant but modest, only 29%, reduction, over untreated plots and other times has had no significant effect on weed populations (Fennimore et al 2013, Zavatta et al 2014.…”
Section: Anaerobic Soil Disinfestationmentioning
confidence: 99%
“…One disadvantage of anaerobic soil disinfestation is its variable weed control, (Zavatta et al 2014). In multiple California field trials anaerobic soil disinfestation has shown significant but modest, only 29%, reduction, over untreated plots and other times has had no significant effect on weed populations (Fennimore et al 2013, Zavatta et al 2014. Applications of anaerobic soil disinfestation with molasses have provided good control of nutsedge and excellent control of grass and broadleaf weeds in sub-tropical Florida where soil temperatures are warmer during anaerobic soil disinfestation (Rosskopf et al 2010).…”
Section: Anaerobic Soil Disinfestationmentioning
confidence: 99%